PENGALAMAN HAMIL PRANIKAH DI USIA REMAJA - Elfira " Deswita; Misrawati " "; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractThe adolescent age is known as the transition period that has different growing process with the childhood and the adult. Teenage pregnancy is the high risk situation. The risk of teenage pregnancy caused of the pschology or mentality and the reproductive organs are still immature and imperfect. This condition will influence to the kids and teenagers who were born. The purpose of this research is to explore the experience of teenage pregnancy. This research used qualitative method with phenomenology approach. This research was conducted to the females who have the experience of teenage pregnancy (less than 19 years) which conducted in working area of Community Health Center (Puskesmas) Bukit Kapur especially in Bagan Besar Village – Dumai City. There were 4 participants involved in this research by using purposive sampling technique according to inclusion criteria. This research used interview guidance. The analysis used was thematic analysis. This research found 5 themes, namely : the feeling of the teenagers when they knew were pregnant, their responses for their first  pregnancy, the impact of premarital pregnancy and their family responses, their expectation for the future. Based on this research, show that it’s needed for the nurses to do counseling about the risk of teenage pregnancy. Keywords: Experience, pregnant, teen age.